PERFORMANCE MAP MEASUREMENT, ZERO-DIMENSIONAL MODELLING & VIBRATION ANALYSIS OF A SINGLE CYLINDER DIESEL ENGINE - GÜL, MEHMET ZAFER (YILDIZ TECHNICAL UNIV, 2017)
Single Cylinder Diesel Engines are simple and very economical in manufacturing. Their multipurpose usability and the capability to deliver the maximum power possible within a given envelope makes them very demanding engines in the market. Simulation tools are widely used nowadays to minimize the energy and time needed for a real engine design and development. Zero-dimensional models are very suitable and reliable to observe the engine operation under different conditions. Contrary to the previous studies, this paper presents a comparison between the practical and simulation model data of a single cylinder Diesel Engine. The purpose of this research was to investigate the fundamental variations between the simulation and experimental results with the help of characteristic engine performance maps. Experiments were conducted on a practical 1.16 L Diesel Engine under variable conditions which were then repeated on the simulation model to analyze and evaluate the differences between the obtained results. Zero-dimensional modelling was performed using GT-Power, a powerful commercial engine simulation software. This study also involved the prediction of optimum speed (RPM) of the engine by performing a vibration analysis using a wireless accelerometer. The maximum torque of the 1.16 L Erin Engine is given to be 80 Nm @ 1,800 RPM, while the simulation model indicated it to be 78 Nm at the same RPM value. Likewise, maximum power output was indicated to be 18 kW @ 2,400 RPM, while the experimental results showed it to be 15 kW @ 2,400 RPM. These results laid down a liable basis for the prediction of several operating parameters of the engine which could act as a solid rung for further studies on this subject.
Keywords: Single-cylinder; Diesel Engines; Zero-dimensional Model; Combustion Analysis; Engine Maps; Vibration Analysis; COMBUSTION MODEL; PREDICTION; SIMULATION; EMISSIONS